2017
DOI: 10.1186/s40854-017-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and cross-section of the day-of-the-week effect

Abstract: We study the day-of-the-week effect across size deciles and in three 18-year subperiods. The results show a decline in the magnitude of the day-of-the-week effect, but the effect did not vanish. We find that the decline in the magnitude of the effect is larger in the larger market capitalization deciles. We also find substantial evidence that the day-of-the-week effect is characterized by a pattern of monotonically improving returns during the week, but the pattern is interrupted as market capitalization incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…This finding may be due to the relatively high financial leverage and lower productivity during downturns (e.g., Kim and Burnie, 2002). Overall, our findings contradict studies claiming that the size premium has disappeared over time (e.g., Hirshleifer, 2001), and those maintaining that the Monday effect is not as significant in recent data (Zilca, 2017).…”
Section: Introductioncontrasting
confidence: 99%
“…This finding may be due to the relatively high financial leverage and lower productivity during downturns (e.g., Kim and Burnie, 2002). Overall, our findings contradict studies claiming that the size premium has disappeared over time (e.g., Hirshleifer, 2001), and those maintaining that the Monday effect is not as significant in recent data (Zilca, 2017).…”
Section: Introductioncontrasting
confidence: 99%
“…In the Indian market, anomalies of day-of-the-week and turn-of-the-month were concluded to exist by Wats (2019). Day-of-the-week effect means that the movement of stock prices is different for some days of the week (Zilca, 2017) while turn-of-the-month means that stock prices increase in the last few days or the first few days of each month (Wats, 2019). To check if the effect of the mentioned anomalies exists for the period of estimating the expected return, the following model was tested:…”
Section: Methodsmentioning
confidence: 99%
“…The day-of-the-week effect is observed in capital markets where certain days exhibit distinct patterns in terms of volatility and returns (Luxianto et al, 2020). Researchers and investors have been interested in this effect as it can offer insights into market dynamics and potentially impact trading strategies (Zilca, 2017). Studies have shown that specific days of the week may experience higher or lower levels of market activity and price movements, indicating the day-of-the-week effect in both volatility and return equations (Chaouachi & Dhaou, 2020;Paital & Panda, 2018).…”
Section: Sonal Sahumentioning
confidence: 99%